Interaksi Sosial Mahasiswa Generasi Z Di Instagram : Analisis Dramaturgi - Sabrina, Uray Nada; Hayati, Kumala (Universitas Pakuan, 2025)
SOCIAL INTERACTION OF GENERATION Z STUDENTS ON INSTAGRAM: A DRAMATURGY ANALYSISInstagram, with 84.6% of users in Indonesia, is one of the primary social media platforms for social interaction. The phenomenon of multiple account ownership is common among Generation Z (born 1997-2012), where each account has a different function, purpose, and form of interaction, creating a role-playing environment for each